Kistadenoma Ovarium Serosum pada Kehamilan: Laporan Kasus pada Wanita Primigravida 23 Tahun dengan Kehamilan Aterm - Isbach, Galuh Prasasti; Hapsari, Fikhy Rizky; Permadi, Danang Pramudya (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background: An ovarian cyst is a sac that contains a search that forms in the ovaries. Ovarian cysts often go undiagnosed due to the asymptomatic or asymptomatic nature of the cyst. In pregnancy, the incidence of ovarian cysts ranges from 0.9%-8.8%. The occurrence of cysts in pregnancy can cause various risks that can harm the mother and fetus. Confirmation of cyst diagnosis can be done using ultrasound imaging and tumor markers based on the type of cyst present. The purpose of this case report is to present symptoms, signs, labolatorium results, histological results of anatomical pathology, and intraoperative findings of a case of sinistra ovarian cyst in women G1P0000 23 years of age with a gestational age of 39-40 weeks. Case Report: : A 23-year-old pregnant woman with a gestational age of 39-40 weeks was referred from the health center for examination at the hospital obstetrics and gynecology polyclinic with suspicion of ovarian cysts. The patient felt symptoms of an enlarged abdomen since 2 years ago and carried out an examination at a health facility, but the findings did not lead to cysts, only complaints on the patient's stomach. The patient only realized the presence of a cyst at 19-20 weeks gestation with a size of 12x12 cm after an imaging examination using ultrasound. There were no signs of distress in either the mother or the fetus in the womb until the patient was re-examined at the hospital at 39-40 weeks gestation. Then, the patient was treated with sectio caesarean section + salfingooovorectectomy with the outcome of the mother and baby being good without any abnormalities. Conclusion: Diagnosis of adnexal masses in pregnancy should be done early to prevent complication in both the mother and the fetus.